Analysis of an E-shaped patch antenna - Pandey V.K.; Vishvakarma B.R. (My University, 2025)
This paper presents the theoretical and simulation investigations of an E-shaped patch antenna applicable in modern mobile communications. It shows marked improvement in the bandwidth when compared with rectangular patch antenna with acceptable radiation pattern. Further, the bandwidth is optimized with respect to notch length, width, and position. Typically, the antenna shows an enhanced impedance bandwidth of 32.5%. © 2006 Wiley Periodicals, Inc.